The Impact of Management Information Systems and Technological Innovation on Organizational Productivity: A Literature Review - Sarianja, Suherdian Septa; Veri, Jhon (UPI YPTK Journal of Business and Economics, 2025)
The main objective of this study is to explore the relationship between management information systems, technological innovation, and accounting education in the context of financial statement preparation practices. The literature search process was conducted using seven keyword combinations: (1) Management Information Systems AND Organisational Productivity, (2) Technological Innovation AND Organisational Performance, (3) Impact of IT Systems on Business Efficiency, (4) Role of Information Technology in Organizational Growth, (5) Digital Transformation AND Business Performance, (6) Enterprise Resource Planning (ERP) AND Productivity (7) Business Intelligence AND Organisational Efficiency. From this search, 1 article was found in Web of Science journals, 2 articles in Elsevier journals, 3 articles in Springer journals, 1 article in Willey-Blackweell journals, 2 articles in Taylor & Francis journals, 2 articles in SAGE Publications journals, 4 articles in Emerald journals, 2 articles in ProQuest journals, 1 article in Ebsco journals and 2 articles in MDPI journals. The literature review results indicate Management Information Systems (MIS) contribute significantly to organisational productivity by enhancing data management, improving decision-making processes, and increasing operational efficiency. Technological innovation drives productivity growth by automating business processes, improving workflow efficiency, and fostering adaptability in rapidly changing markets.